Deconstructing chronic low back pain in the older adult—Step by step evidence and expert‐based recommendations for evaluation and treatment part III: Fibromyalgia syndrome. Issue 9 (14th August 2015) - Fatemi, Gita; Fang, Meika A.; Breuer, Paula; Cherniak, Paul E.; Gentili, Angela; Hanlon, Joseph T.; Karp, Jordan F.; Morone, Natalia E.; Rodriguez, Eric; Rossi, Michelle I.; Schmader, Kenneth; Weiner, Debra K.
Abstract: Objective: To present the third in a series of articles designed to deconstruct chronic low back pain (CLBP) in older adults. The series presents CLBP as a syndrome, a final common pathway for the expression of multiple contributors rather than a disease localized exclusively to the lumbosacral spine. Each article addresses one of 12 important contributors to pain and disability in older adults with CLBP. This article focuses on fibromyalgia syndrome (FMS). Methods: A modified Delphi approach was used to create the evaluation and treatment algorithm, the table discussing the rationale behind each of the algorithm components, and the stepped‐care drug recommendations. The team involved in the creation of these materials consisted of a principal investigator, a 5‐member content expert panel, and a 9‐member primary care panel. The evaluation and treatment recommendations were based on availability of medications and other resources within the Veterans Health Administration (VHA) facilities. However, non‐VHA panelists were also involved in the development of these materials, which can be applied to both VA and civilian settings. The illustrative clinical case was taken from the clinical practice of the principal investigator. Results: Following expert consultations and a review of the literature, we developed an evaluation and treatment algorithm with supporting materials to aid in the care of older adults with CLBP who have concomitant FMS. A case is presented that demonstrates the complexity of pain evaluation and management in older patients with CLBP and concomitant FMS. Conclusions: Recognition of FMS as a common contributor to CLBP in older adults and initiating treatment targeting both FMS and CLBP may lead to improved outcomes in pain and disability.